Analisis Dan Pemodelan Motor Induksi Tiga Fasa Delapan Kutub Dengan Rangkaian Ekivalen Invers Г - Sukma, Dian Yayan; Rafli, Silvia; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This study aimed to analyze and modelling an induction motor. The motor is used in this study is three phases induction motor eight poles, 500 W, 30 V, 50 Hz and 750 rpm. In this study the equivalent circuit is form into an inverse Г transformation equations of three phases induction motor. The porpose of this study is to create a model of three phases induction motor eight poles using inverse Г equivalent circuit, analyzing equations and equivalent circuit models obtained using matlab application, and comparing the results with the results of the actual testing analyst induction motor three phases eight poles.Analysts done on two conditions, no load and load. From direct testing and analysis results were found comparisons percent error of the test results and analysis of induction motor three phases eight poles, there are input voltage when starting is 11%, starting current 23,21%, the influence load to voltage is 2,9%, the effect of load on the starting current 24,3% and during the current reduce is 26%. The percent error is quite high, this is cause errors in measurement parameters.Keyword : Induction Motor Three Phases, Inverse Г Equivalent circuit, Parameters